Design, fabrication and characterization of undoped-GaN based pH sensor [electronic resource] - Maneea Eizadi Sharifabad, 1982- (2010)
Thesis (Sarjana Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2010